2015
DOI: 10.1007/s11103-015-0384-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic changes following synthesis of a Populus full-sib diploid and allotriploid population with different heterozygosities driven by three types of 2n female gamete

Abstract: Diploid gametes are usually applied to produce triploids of Populus [originating from first-division restitution (FDR), second-division restitution (SDR), and postmeiotic restitution (PMR) 2n eggs]. Three types of 2n gametes transmitted different parental heterozygosities in Populus. Failed spindle formation and no chromosomal separation to opposite poles during meiosis I mean that FDR 2n gametes carry nonsister chromatids that are potentially heterozygous. By contrast, SDR 2n gametes result from failed sister… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 78 publications
(101 reference statements)
0
20
0
Order By: Relevance
“…Afterward, many studies looking at the artificial induction of polyploid began [14,21,46], and many excellent results were obtained in the last 10 years [27][28][29][30][31][32][33]. Previous research has shown that polyploid breeding is more successful upon utilization of heterosis [47][48][49]. To realize the comprehensive utilization of the dosage effect and heterosis in Eucalyptus, a more reasonable process could be to obtain triploids by sexual polyploidization.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, many studies looking at the artificial induction of polyploid began [14,21,46], and many excellent results were obtained in the last 10 years [27][28][29][30][31][32][33]. Previous research has shown that polyploid breeding is more successful upon utilization of heterosis [47][48][49]. To realize the comprehensive utilization of the dosage effect and heterosis in Eucalyptus, a more reasonable process could be to obtain triploids by sexual polyploidization.…”
Section: Discussionmentioning
confidence: 99%
“…Forests 2019, 10, 1091 3 of 13 'Beijingensis'. Allo-triploids namely FDR, SDR and PMR were previously generated from the 2n hybrid F1 [2,3,13]. Briefly, the FDR population is generated from male gametes and non-reduced egg gametes in which chromosomes do not move to the opposite poles during meiosis I.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The SDR population is generated from male gametes and non-reduced egg gametes in which no cell plate is formed during sister chromatid separation in meiosis II. The PMR population is generated from male gametes and non-reduced egg gametes in which chromosomes are duplicated after meiosis [2,3,13]. The apical buds were collected from 15 individuals of 2n hybrid F1 Populus, and 15 individuals from each of three allo-triploid populations namely FDR, SDR and PMR, and 15 individuals from their parental progenitors.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations